Maze board design for introducing Javanese vocabulary krama inggil in children aged 4-6 years - Rosida, Nayla Ahsana; Bahri, Nurul Fitriana (Gelar : Jurnal Seni Budaya, 2024)
This study addresses the lack of introduction to the Javanese Krama Inggil language among children aged 4-6 years in the environment of RA Hidayatut Thullab located in Trenggalek district, East Java. This decline occurred due to several things, such as the lack of introduction to the Javanese Krama Inggil language from an early age, globalization, and environmental factors that could lead to the extinction of the language. This research was carried out as an implementation of efforts to preserve culture through educational games. This research aims to increase children's interest in the Javanese Krama Inggil language through educational game. The basis for this research uses data regarding the stages of language development and play stages of children aged 4-6 years. Apart from that, anthropometric data is also used as a basis for designing educational game tools that suit the size of the child's hand so that the child can play comfortably. Interview and observation methods were carried out with teachers at RA Hidayatut Thullab. During the study, interviews were conducted to identify the learning media requirements in schools and how language learning is carried out. Additionally, non-participant observation was carried out for four days to identify problems, such as the children's ability to communicate using Javanese Krama Inggil. The research results show that RA Hidayatut Thullab students only use basic Javanese Krama Inggil or not at all in their daily activities. The findings of this research highlight the decreasing number of speakers of Javanese Krama Inggil due to a lack of early introduction to the language. Therefore, schools need to involve local content as an effort to introduce regional languages to children from an early age. To make the learning process more interesting and enjoyable, media is needed that can help children recognize and learn regional languages.